EVALUASI KINERJA BONGKAR MUAT DI PELABUHAN UMUM GRESIK - Raekhan, M. Rum; Djakfar, Ludfi; Pujiraharjo, Alwafi (Jurnal Transportasi, 2017)
Abstract This study aims to determine the performance of the ship loading and unloading in the Port of Gresik especially on Pier 265, Bulk Dry Pier and Pier 70. The analysis method used in this research is descriptive analysis method, Importance Performance Analysis and Quality Function Deployment. Based on the results of descriptive analysis is known that the problems that cause idle time are: waiting trucks, loading and unloading equipment failures, labor disputes, waiting for a load and due to the weather. Based on the Importance Performance Analysis, there are variables deemed important but the performance is still low are: the speed of loading and unloading process, readiness of truck, stacking yard capacity, the cleanliness of the harbor and lighting problems. Based on the analysis of QFD there are several priority issues handling the loading and unloading of which ensure the readiness of cargo to be loaded, the use of warehouses in an optimal, ensuring readiness of loading and unloading equipment, providing fresh gang in order to operate 24 hours, expansion of the yard, speeding up the transport of goods in yard, the ship that will carry out loading and unloading must determine transportation management services, add lighting and improve the cleanliness of the harbor area. Keywords: loading and unloading, performance, IPA, QFD Abstrak Penelitian ini bertujuan untuk mengetahui kinerja bongkar-muat di Pelabuhan Umum Gresik khususnya pada Dermaga 265, Dermaga Curah Kering, dan Dermaga 70. Metode analisis yang digunakan dalam penelitian ini adalah metode analisis deskriptif, Importance Performance Analysis (IPA) dan Quality Function Deployment (QFD). Dari hasil analisis, kinerja bongkar-muat diketahui bahwa produktivitas bongkar-muat rata-rata baik sedangkan ET:BT (efektif time:berthing time) masih kurang baik. Selain itu, masalah yang banyak menyebabkan idle time diantaranya: penting namun kinerjanya masih rendah, yaitu kecepatan dalam proses bongkar-muat, kesiapan truck, kapasitas lapangan penumpukan, kebersihan area pelabuhan dan masalah penerangan. Berdasarkan hasil analisis QFD ada beberapa prioritas dan urutan prioritas dalam penanganan permasalahan bongkar-muat diantaranya memastikan kesiapan muatan yang akan dimuat, penggunaan gudang secara optimal, memastikan kesiapan alat bongkar-muat, penyediaan fresh gang untuk tenaga bongkar-muat agar bisa beroperasi 24 jam, perluasan lapangan penumpukan, mempercepat pengangkutan barang yang ada di lapangan penumpukan, kapal yang akan melakukan bongkar-muat harus menentukan jasa pengurusan transportasi dengan jumlah truk yang cukup, menambah lampu penerangan, dan meningkatkan kebersihan area pelabuhan. Kata-kata kunci: bongkar-muat, kinerja, IPA, QFD